Examining the Moderating Effects of Masculinity Threat between the Precarious Manhood Belief and Level of Amusement on Sexist Jokes - Gamboa, Haryn Mardy A.; Lara, Aileen D.; Abuyo, Madelle L. (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2022)
The study aimed to determine the relationship between Precarious Manhood Beliefs (PMB) and man's level of amusement (LOA) in sexist jokes through the moderating effect of masculinity threat.The researchers used standardized instruments to identify the PMB levels and Amusement levels on Sexist Jokes of 156 participants who are 18 years old and above, male heterosexual 4th year college students at selected universities around Laguna and Batangas. The data gathered were analyzed through Independent Sample T-test, Pearson’s R and Moderation Analysis through Process by Hayes. The results of the study showed that heterosexual males under the threat condition had a higher level of PMB and LOA in sexist jokes. Heterosexual males under the threat condition have higher LOA in sexist jokes. There was no significant difference in the scores for the threat condition and non-threat condition in terms of PMB. On the other hand, there is a significant difference in the scores for the threat condition non-threat condition in terms of LOA in sexist jokes. The findings also indicated a significant relationship between PMB and LOA in sexist jokes. Masculinity as the moderator in this research strengthens the relationship of Precarious Manhood Belief and Level of Amusement in sexist jokes.By further analyzing the relationships of the variables, this thesis assumes that males who have a high level of PMB are under the pressure of following the societal standards of "masculinity" to prove they are "real men".